2022
DOI: 10.3390/ijerph191710959
|View full text |Cite
|
Sign up to set email alerts
|

All-People-Test-Based Methods for COVID-19 Infectious Disease Dynamics Simulation Model: Towards Citywide COVID Testing

Abstract: The conversion rate between asymptomatic infections and reported/unreported symptomatic infections is a very sensitive parameter for model variables that spread COVID-19. This is important information for follow-up use in screening, prediction, prognostics, contact tracing, and drug development for the COVID-19 pandemic. The model described here suggests that there may not be enough researchers to solve all of these problems thoroughly and effectively, and it requires careful selection of what we are doing and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…took the conversion rate between asymptomatic infections and reported/unreported symptomatic infections into account, and proposed an infectious dynamics model that adapts to all-people testing (APT). It adapted to densely populated metropolises for APT on prevention, where the result seemed more reasonable, and epidemic prediction became more accurate [25] . The primary limitation of these compartmental models is that they are subject to assumptions about the transmission process and the parameters.…”
Section: Related Workmentioning
confidence: 99%
“…took the conversion rate between asymptomatic infections and reported/unreported symptomatic infections into account, and proposed an infectious dynamics model that adapts to all-people testing (APT). It adapted to densely populated metropolises for APT on prevention, where the result seemed more reasonable, and epidemic prediction became more accurate [25] . The primary limitation of these compartmental models is that they are subject to assumptions about the transmission process and the parameters.…”
Section: Related Workmentioning
confidence: 99%
“…Nowadays, several researchers are searching for antique and new tools in data analysis to modeling and forecasting studies applied in this pandemic. The epidemic analysis for forecasting COVID-19 using, among others, the susceptible, infected, and recovered (SIR) [ 2 ], susceptible, infected, recovered, and deceased (SIRD) [ 3 ], susceptible, exposed, infected, and recovered (SEIR) [ 4 ], susceptible, exposed, infected, recovered and dead (SEIRD) [ 5 ], SEIRD model with the compartment of vaccinated people (SEIRDV) [ 6 ], and Moving Average [ 7 ] models, or even hybrid dynamic model as is SEIRD with Automatic Regressive Integrated Moving Average (ARIMA) corrections [ 8 ] or data-driven hybrid technique by integrating an ensemble empirical mode decomposition (EEMD), an autoregressive integrated moving average (ARIMA), with a nonlinear autoregressive artificial neural network (NARANN), called the EEMD-ARIMA-NARANN model [ 9 ]. Predictive models of mortality have also been studied, highlighting the study of Friedman et al [ 10 ], which observed that seven COVID-19 models covered more than five countries, suggesting that effects of seasonality or continued slow [ 11 , 12 , 13 , 14 , 15 , 16 , 17 ] declines in mortality could be responsible for converging in their predictions for the June–August 2020 period.…”
Section: Introductionmentioning
confidence: 99%